Moving Beyond the Green Wall: Overcoming Environmental Pressures - Subramanian, K. R. (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2017)
In response to business environment several organizations in the last few decades added a department having responsibility to deal with environmental related issues. Mostly the activities were dominated by legal and regulatory action and the end-of-the-pipe, technically based solutions to these issues. Their position and authority rarely offered the potential for lending value to the firm; more often, they were viewed as a cost center by top management. When businesses’ responses to environmentalism have been tied to core business decisions, however, a great deal of organizational change has been required— including overcoming the “Green Wall” between early treatment of environmental issues and the language, tools, and culture of business. Corporate leaders have been driven to evolve over time from early focus on industrial, regulatory, and social responsibility toward a mindset of the natural environment as strategic in nature. This recognition is increasingly important, especially with the rise of broader sustainable development and corporate social responsibility concerns. This recognition is increasingly important, especially with the rise of broader sustainable development and corporate social responsibility concerns. Clearly, environmental management and strategy has reached the executive level in many larger businesses, yet often the Green Wall remains a deeply rooted cultural obstacle in organizations.